PERBEDAAN EFEKTIVITAS PEMBERIAN AIR REBUSAN DAUN ALPUKAT DAN DAUN SELEDRI TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI - Ratna Monita Dewi; Elmie Muftiana; Dian Laila Purwaningroom (Health Sciences Journal, 2022)
Hypertension is a condition where there is an increase in systolic pressure of more than 140 mmHg and diastolic pressure of more than 90 mmHg. The elderly have a high risk of suffering from high blood pressure. There are therapies that are often used for people with hypertension, including the therapy of boiled avocado or celery leaves. The purpose of this test is to test the effectiveness of avocado or celery leaf decoction therapy in lowering blood pressure in the elderly with hypertension.This research uses Quasi Experiment and Pretest Posttest Control Group Design. The sampling stage is purposive sampling, where in this study with a sample of 16 people and will be divided into two groups, with 8 people in avocado leaf stew and the remaining 8 people in celery stew.The results of the study using the Paired T test showed that the difference in mean systole and diastole after being given boiled avocado leaves was 15.25 and 11.7, while the difference in mean systole and diastole after being given boiled celery was 11.4 and 10.95. While the results of the Independent T test of the comparison of the intervention and control groups obtained a systolic p-value = 0.015 (0.05) and a diastolic p-value = 0.001 (0.05), which means that there is an effectiveness of avocado or celery leaf decoction therapy in lowering blood pressure in elderly with hypertension.Based on this study, avocado leaves and celery both can lower blood pressure in the elderly with hypertension, but the results show that avocado leaf decoction is proven to be more effective in lowering blood pressure than celery. With these results, it is hoped that it can be used as a reference for therapy for the elderly with hypertension other than drugs.